2010
DOI: 10.2224/sbp.2010.38.6.795
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of straybirds agricultural trainees in taiwan

Abstract: The Straybirds program is the most important agricultural training plan in Taiwan, aimed at attracting a young labor force capable of efficient production to engage in careers in farming. In this paper we investigate the associations between psychological factors and behaviors of Straybirds trainees, using a survey of 316 participants conducted in 2007. A structural equation model was used to examine causal relationships between the level of agricultural knowledge, attitudes, and practices of the college train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Pesticide use knowledge is crucial for workers, and they should be aware to protect themselves. 28 -31 In this study, some workers went to traditional medicine after pesticide exposure and it was also recorded from a previous study conducted in Ethiopia, 21 this suggests that workers were less aware of the negative impacts of pesticides. Recognizing early indications of pesticide overexposure, and obtaining first aid at the earliest time is important.…”
Section: Discussionsupporting
confidence: 56%
“…Pesticide use knowledge is crucial for workers, and they should be aware to protect themselves. 28 -31 In this study, some workers went to traditional medicine after pesticide exposure and it was also recorded from a previous study conducted in Ethiopia, 21 this suggests that workers were less aware of the negative impacts of pesticides. Recognizing early indications of pesticide overexposure, and obtaining first aid at the earliest time is important.…”
Section: Discussionsupporting
confidence: 56%
“…Empirical studies on the knowledge-attitude-practice sequence have shown that people gain knowledge which predisposes them to attitudes that motivate them to practice a certain behavior (Leung, Chan, Fu, & Lam, 2010;Okobia, Bunker, Okonofua, & Osime, 2006;Wang, Huang, & Knerr, 2010). Several theories such as the theory of planned behavior (Ajzen, 1991) and the health belief model (Rosenstock, 1974), which relied on the knowledge-attitude-practice sequence, have also highlighted the role of knowledge as a precursor to the formation of attitudes and practices.…”
Section: Extensions To Behavioral Intentionsmentioning
confidence: 99%
“…Several theories such as the theory of planned behavior (Ajzen, 1991) and the health belief model (Rosenstock, 1974), which relied on the knowledge-attitude-practice sequence, have also highlighted the role of knowledge as a precursor to the formation of attitudes and practices. Although studies that applied the knowledge-attitude-practice sequence have shown that attitudes tend to mediate the influence of knowledge on behaviors (e.g., Sessa, Giuseppe, Albano, & Angelillo, 2011;Wang et al, 2010), empirical evidence have also demonstrated that knowledge can have a direct (albeit small) effect on health behaviors (Chew et al, 2002;Morgan & Miller, 2002;Viswanath, 2006;Yap, Lee, Yau, Ng, & Tor, 2010). For example, Yap and colleagues (2010) demonstrated that knowledge has a significant influence on attitudes and behavioral changes among Singaporeans during the H1N1 pandemic.…”
Section: Extensions To Behavioral Intentionsmentioning
confidence: 99%
“…Studies have focused on the effects of psychological factors on individual behaviors, such as social learning theory, the theory of reasoned action, and the theory of planned behavior [ 18 , 19 ]. Few studies on agriculture have identified associations between farming practices, attitudes, and other psychological determinants [ 13 , 20 ].…”
Section: Introductionmentioning
confidence: 99%